2021
DOI: 10.1038/s41523-021-00258-0
|View full text |Cite
|
Sign up to set email alerts
|

FOXA1 and adaptive response determinants to HER2 targeted therapy in TBCRC 036

Abstract: Inhibition of the HER2/ERBB2 receptor is a keystone to treating HER2-positive malignancies, particularly breast cancer, but a significant fraction of HER2-positive (HER2+) breast cancers recur or fail to respond. Anti-HER2 monoclonal antibodies, like trastuzumab or pertuzumab, and ATP active site inhibitors like lapatinib, commonly lack durability because of adaptive changes in the tumor leading to resistance. HER2+ cell line responses to inhibition with lapatinib were analyzed by RNAseq and ChIPseq to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…We then test whether GBP family gene region is relocated into LLPS zone in the process of immune activation. Based on previous BRD4 and MED1 ChIP-seq data 45 , we found that GBP family genome regions were enriched with these two phase separation marker proteins (Fig. 4d ).…”
Section: Resultssupporting
confidence: 56%
“…We then test whether GBP family gene region is relocated into LLPS zone in the process of immune activation. Based on previous BRD4 and MED1 ChIP-seq data 45 , we found that GBP family genome regions were enriched with these two phase separation marker proteins (Fig. 4d ).…”
Section: Resultssupporting
confidence: 56%
“…These results underscore the requirement for FOXA1 in lapatinib-resistant, HER2+ disease. Patient data support this conclusion where breast tumors with decreased expression of FOXA1 were less proliferative, had reduced ERBB2/ERBB3 (HER2/HER3) expression, and increased enrichment of immune signatures [167]. As a whole, these studies revealed that the function of FOXA1 extends beyond its canonical role of modulating ER activity in breast cancer.…”
Section: Foxa1 Is Required For Lapatinib-resistance In Her2-enriched Breast Cancersmentioning
confidence: 54%
“…Mechanisms of acquired lapatinib (EGFR/HER2 inhibitor) resistance are diverse, including expression of truncated/activated HER2 and elevated PI3K/AKT signaling that lead to dramatic epigenetic and transcriptional changes. Angus et al found that a large number of superenhancers are acquired in the context of lapatinib resistance, including those at the ERBB2 (HER2), PBX1, and FOXA1 genes [167]. They further revealed that the increased expression of FOXA1 is essential for proliferation of lapatinib-resistant cell lines and, in a feed-forward manner, induced the expression of ERBB3 (HER3).…”
Section: Foxa1 Is Required For Lapatinib-resistance In Her2-enriched Breast Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental overexpression of HER2 in mammary epithelial cells in MMTV-Neu transgenic mice is sufficient to produce breast cancers in vivo demonstrating its transforming ability (10, 11). Interestingly, despite low levels of ERα expression, FOXA1 is expressed in many HER2- positive tumors, where its expression correlates with higher rates of cell proliferation (12). It has been proposed that there is cross-regulation between HER2 and FOXA1 in ERα-negative breast tumors involving several other transcription factors, including RELB, PAK1, and TLE3 (13).…”
Section: Introductionmentioning
confidence: 99%